Homage to political philosophy : the good society from Plato to the present - Flynn, James R. 1934- (Cambridge Scholars Publishing, 2018)
"This book offers a model introduction to political philosophy, addressing philosophers from Plato to Rawls and Nozick, with each thinker treated as exploring perennial problems. These include ethical truth, free will, the common good, whether God exists, whether America could become a Hobbesian world sovereign, appeals to nature, free speech, the nature of rights, how one can argue with Nietzsche, whether history is predictable, whether the market can be humanized, and assumed genetic differences between races and genders. When a thinker poses a problem not resolvable at that time, (such as racial equality) modern social science and economics are used to provide answers. There are two persistent themes in this book: namely, that a futile search for ethical truth has drained the original image of the good society (Plato and Aristotle) of its rich content, and that the market has replaced justice as the ordering principle of human society leaving philosophers helpless unless they learn economics."--